VALIDATION OF A SUPPORT SYSTEM ON BUILDING SYSTEM SELECTION IN CONSTRUCTION - Christiono Utomo (Institut Teknologi Sepuluh Nopember (ITS), 2010)
Decisions for multi-person on building system selection are very complicated since many parties involved. Where a number of stakeholders are involved in choosing single alternative from a set of alternatives, there are different concern caused by differing preferences, experiences, and background. Therefore, a support system is required to enable each stakeholder to evaluate and rank the solution alternatives before engaging into negotiation. This paper presents a validation process of the negotiation support system in building system selection. A case study was carried out in a real estate company in Indonesia. Validation was conducted to a framework of coalition formation as a basis algorithm of negotiation support for building system selection in construction. Two methods of validation were conducted in a group decision to select building roof system. These methods are decision result validation by similarity index and stakeholder preferences validation by canonical correlation analysis and a set of descriptive statistic analysis. Two others conventional model were compared with the coalition formation algorithms. This validation process reveals that the algorithms proposed is better than single weight factor and aggregation method in terms of closely to the best fit option, stakeholder satisfaction, and performance of the model.